Territorialidad y autonomía, proyectos minero-energéticos y consulta previa: el caso de los pueblos indígenas de la Amazonia ecuatoriana - García Serrano, Fernando (2014)
From the review of two areas of relative state / indigenous peoples, territoriality, mining and energy projects and consultation, is to analyze the progress, setbacks and dissections lived in this relationshipduring the period 1990-2013, to contribute to the discussion of this problem in other countries experiencing similar circumstancesin Latin America. Of particular importance is the case of Ecuador to the constitutions of 1998 and 2008, in which the multiethnic and multicultural nature of the Ecuadorian State acknowledged at the first, and the plurinational and intercultural character in the second. Likewise, the indigenous movement since its emergence as an actor in national politics since 1990, has not only been a pioneer and leader in the region, but has been challenger extractivismo process carried outby the state.